Synergistic Strategies of Heat and Peroxyacetic Acid Disinfection Treatments for Salmonella Control - Olja Šovljanski; Aleksandra Ranitović; Ana Tomić; Nenad Ćetković; Ana Miljković; Anja Saveljić; Dragoljub Cvetković (Pathogens, 2023)
The food industry has recognized a pressing need for highly effective disinfection protocols to decrease the risk of pathogen emergence and proliferation in food products. The integration of antimicrobial treatments in food production has occurred as a potential strategy to attain food items of superior quality with respect to microbiological safety and sensory attributes. This study aims to investigate the individual and synergistic effects of heat and peroxyacetic acid on the inactivation of bacterial cells, considering various contact times and environmental conditions. Four Salmonella serotypes, isolated from industrial meat production surfaces, were employed as model organisms. By systematically assessing the impacts of individual factors and synergistic outcomes, the effectiveness of bacterial cell inactivation and the efficiency of heat and peroxyacetic acid could be predicted. To better approximate real-world food processing conditions, this study also incorporated a bovine albumin-rich condition as a simulation of the presence of organic loads in processing steps. The findings revealed the essential need for a synergistic interplay of investigated parameters with the following optimized values: 1.5% concentration of peroxyacetic acid, temperature range of 60–65 °C, and contact time of 3 min for the complete effect regardless of the degree of contamination.